Analisis kinerja rumah sakit dengan pendekatan balanced scorecard pada RSI surabaya - Safitri, Shinta; Prastiwi, Dewi; Setianto, Budhi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to measure the performance of the Surabaya Islamic Hospital with a balanced scorecard approach. The balanced scorecard approach consists of perspectives, finance, customers, internal business processes, as well as growth and learning. The research was carried out with descriptive qualitative methods. The primary data collection method was conducted by interviewing the HR section, the medical record unit, and the nursing section. Secondary data used in this study is data and information from the web, journals, books and documents related to hospital performance measurement, in the form of financial reports and patient care data. The results of the study can be concluded from a financial perspective, it is considered good except for the liquidity ratio. Customer perspective is considered good. The internal business process perspective is considered good, all except the BTO parameter. Growth and learning perspectives are considered good.